The Influence of Entrepreneurial Education on Individual Entrepreneurial Orientation of University Students: A Systematic Review - Daniella Teles Amaral (LPPM of NAROTAMA UNIVERSITY, 2023)
The level of entrepreneurship in a country is an important determinant of economic growth and success. However, it is essential to ensure that individuals are gaining the necessary knowledge and skills to choose an entrepreneurial career upon completion of their studies. A qualitative research approach was employed by systematically reviewing approaches to entrepreneurial education and their effect on an individual’s entrepreneurial orientation. Data were analysed by means of thematic content analysis. Articles were identified in prominent databases according to a set of inclusion and exclusion criteria. The findings were grouped into six themes: The importance of the practical nature of entrepreneurial education; the impact of entrepreneurial education on the economy; entrepreneurial education approaches; the importance of individual entrepreneurial orientation; common individual entrepreneurial orientation factors and the interchangeability of individual entrepreneurial orientation, intrapreneurial orientation, and entrepreneurial attitude orientation. The findings of the systematic review indicate that there is a gap in the current body of knowledge, and the value of the study lies in the fact that many studies have explored the influence of entrepreneurial education on the intention of students, but very few have analysed this influence based on a student’s individual entrepreneurial orientation. Furthermore, findings also reveal that current entrepreneurial education approaches employ theory-based teaching but do not place enough emphasis on practice-based teaching. The findings of this study contribute to the existing body of knowledge by investigating the influence that entrepreneurial education has on the individual entrepreneurial education of university students.